Platelet GPVI (Glycoprotein VI) and Thrombotic Complications in the Venous System. Issue 11 (9th September 2021) - Perrella, Gina; Nagy, Magdolna; Watson, Steve P.; Heemskerk, Johan W.M.
Abstract : The immunoglobulin receptor GPVI (glycoprotein VI) is selectively expressed on megakaryocytes and platelets and is currently recognized as a receptor for not only collagen but also a variety of plasma and vascular proteins, including fibrin, fibrinogen, laminin, fibronectin, and galectin-3. Deficiency of GPVI is protective in mouse models of experimental thrombosis, pulmonary thromboembolism as well as in thromboinflammation, suggesting a role of GPVI in arterial and venous thrombus formation. In humans, platelet GPVI deficiency is associated with a mild bleeding phenotype, whereas a common variant rs1613662 in the GP6 gene is considered a risk factor for venous thromboembolism. However, preclinical studies on the inhibition of GPVI-ligand interactions are focused on arterial thrombotic complications. In this review we discuss the emerging evidence for GPVI in venous thrombus formation and leukocyte-dependent thromboinflammation, extending to venous thromboembolism, pulmonary thromboembolism, and cancer metastasis. We also recapitulate indications for circulating soluble GPVI as a biomarker of thrombosis-related complications. Collectively, we conclude that the current evidence suggests that platelet GPVI is also a suitable cotarget in the prevention of venous thrombosis due to its role in thrombus consolidation and platelet-leukocyte complex formation.